(untitled) (Public Sector Economics - submission site, 2021)
This paper quantifies the impact of grants from EU funds on non-financial corporations performance in Croatia. For the purposes of the research, three different data sources were used, which were merged into a single enterprise level database. Enterprises for the control group were selected using propensity score matching method, while the quantifications of effects in the years after receiving the support were estimated using difference in differences method. Also, the doseresponse relationship between the relative size of the received grant and the level of impact on performance indicators was assessed. The research showed that the use of EU funds has a strong and positive effect on the observed indicators, such as employment, operating income, labour productivity or total factor productivity and capital intensity. At the same time, the level of impact significantly depends on the relative size of grant received from EU funds.